Sistemas de control gerencial y productividad en las agencias de turismo de la ciudad de Yurimaguas 2020 - Cachique Chota, Jack Henderson (2021)
The purpose of the research report was to determine the degree of relationship between the management of management control systems and productivity in the tourism agencies of the city of Yurimaguas, 2020; Being the non-experimental design of a descriptive correlational type, 6 managers were taken as a sample, who were surveyed by means of a questionnaire with questions as an instrument; Therefore, the work concludes that the management of management control systems in agencies is adequate, since they sometimes carry out a business diagnosis, also planning sometimes contemplates the mission and objectives of the entity, almost always handles daily information on income and expenses, allowing the clear presentation of financial statements, and almost always handles updated information on the online strategy. Likewise, productivity in the tourism agencies of the city of Yurimaguas is adequate, since the staff is shown to be committed to their work, they are also almost always clear about the skills and capacities of the position, but only sometimes they receive training, the staff always meet objectives and almost always have a well-developed budget. Finally, it was determined that the management control system is significantly related to productivity, being contrasted by a relationship (Pearson) of 0.962 which is positive and high, in addition to a degree of significance of 0.002.